Simplex Lattice Approach to Optimize Yields of Light Oil Products from Catalytic Cracking of Bio-Oil with Mixed Catalysts - Jaroenkhasemmeesuk C. (2017)
© 2017, Copyright © Taylor & Francis Group, LLC. Bio-oil is a potential product from the fast pyrolysis of biomass. However, it should be upgraded before being used in subsequent applications and corrosion prevention. In this work, crude bio-oil from fast pyrolysis of Jatropha curcas residues, which has many long-chain compounds, and a high content of carboxylic acid, was catalytically upgraded over mechanically mixed catalysts (normal ZSM-5 and Y-Re-16) in a fixed-bed reactor. The effects of the key parameters on the yields of light oil products were analyzed, including cracking temperature (350–500°C), reaction time (15–60 min), catalyst loading (10–25%), and mixture ratio between Y-Re-16 and ZSM-5 (10–70%). Experimental test cases were based on a simplex lattice design. The gas chromatograph-mass spectrometer (GC-MS) analysis showed that the catalytic cracking of crude bio-oil using mixed catalysts resulted in the successful formation of short-chain acid methyls. The employed analytical fit of the experimental data gave R 2 and the adjusted R 2 of 0.902 and 0.843, respectively. The optimized operation conditions to produce aliphatic hydrocarbons from mechanically mixed catalysts were found to be at 400°C, 15 min of reaction time, 15% of catalyst loading, and a mixture ratio of about 1:5.